An Adaptive Management Framework Concept for the Sustainable Use of the Saker Falcon - Andras Kovacs; Colin Galbraith; Robert Sheldon; Umberto Gallo-Orsi; Lauren Lopes (Пернатые хищники и их охрана)
The Saker Falcon (Falco cherrug) is listed on the International Union for Conservation of Nature (IUCN) Red List as Globally Endangered. It breeds across continental middle latitudes, with its range spanning over 7,000 km from Central Europe to Western China, and 3,000 north to south. Most populations are migratory and a number of different routes have been confirmed by field observations and satellite tracking. One of the principal threats affecting its global population is unsustainable trapping/harvest on the breeding grounds and along the migration routes. The Saker Falcon is listed in Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), which enables trade subject to the development of a Non-Detriment Finding (NDF).